Interpretation of 'Unnatural Death' in Coronial Law: A Review of the English Legal Process of Decision Making, Statutory Interpretation, and Case Law: The Implications for Medical Cases and Coronial Consistency. (23rd April 2018) - Harris, Andrew; Walker, Andrew
Abstract: The article examines the decision-making process for medical reporting of deaths to a coroner and the statutory basis for coronial decisions whether to investigate. It analyses what is published about the consistency of decision making of coroners and discusses what should be the legal basis for determining whether a particular death is natural or unnatural in English law. There is a review of English case law, including the significance of Touche and Benton and the development of 'unnatural' as a term of art, which informs what the courts have held to be an unnatural death. What case law indicates about multiple causes and the significance of the wording in the Coroners & Justice Act 2009 that triggers an investigation are considered. It highlights the importance of considering the medical cause of death and to what extent information other than the initial death report is required, before making the decision that the coroner's duty to open an investigation is triggered. The article concludes that a two-stage test is required. Firstly, is the cause of death medically unnatural? Secondly, whether the circumstances themselves are unnatural or such as to make a medically natural cause of death unnatural. If the coroner has reason to suspect the medical cause of death is unnatural per se the statutory duty to investigate will be engaged, regardless of the circumstances.